2023
DOI: 10.1002/jbt.23325
|View full text |Cite
|
Sign up to set email alerts
|

The advance anticancer role of polymeric core‐shell ZnO nanoparticles containing oxaliplatin in colorectal cancer

Abstract: We evaluated the activity of core‐shell ZnO nanoparticles (ZnO‐NPs@polymer shell) containing Oxaliplatin via polymerization through in vitro studies and in vivo mouse models of colorectal cancer. ZnO NPs were synthesized in situ when the polymerization step was completed by co‐precipitation. Gadolinium coordinated‐ZnONPs@polymer shell (ZnO‐Gd NPs@polymer shell) was synthesized by exploiting Gd's oxophilicity (III). The biophysical properties of the NPs were studied using powder X‐ray diffraction (PXRD), Fourie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 108 publications
0
3
0
Order By: Relevance
“…ZnO nanoparticles conjugated with N-succinyl chitosan showed strong anticancer activities on breast cancer cells (MDA-MB-231) by inducing apoptotic action ( Ghaffari et al, 2020 ). The treatment of ZnO nanoparticles containing Oxaliplatin via polymerization showed strong anticancer action on colorectal cancer cells, as examined in both in vitro studies and in vivo mouse models ( Alavi et al, 2023 ). In addition, the treatment of pure ZnO nanoparticles and doped with molybdenum and graphene oxide nanoparticles showed anticancer activity on the human colon (HCT116) and breast (MCF7) cancer cells, and anticancer action was mediated through reactive oxygen species, p53, and the caspase-3 pathway ( Ahamed et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…ZnO nanoparticles conjugated with N-succinyl chitosan showed strong anticancer activities on breast cancer cells (MDA-MB-231) by inducing apoptotic action ( Ghaffari et al, 2020 ). The treatment of ZnO nanoparticles containing Oxaliplatin via polymerization showed strong anticancer action on colorectal cancer cells, as examined in both in vitro studies and in vivo mouse models ( Alavi et al, 2023 ). In addition, the treatment of pure ZnO nanoparticles and doped with molybdenum and graphene oxide nanoparticles showed anticancer activity on the human colon (HCT116) and breast (MCF7) cancer cells, and anticancer action was mediated through reactive oxygen species, p53, and the caspase-3 pathway ( Ahamed et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…These nanoparticles could cross the blood-brain barrier and accumulate in the brain, causing oxidative stress, DNA damage, and inflammation in neural cells. These neurotoxic effects raised concerns regarding their potential impact on the overall system's overall health [116].…”
Section: Genotoxicitymentioning
confidence: 99%
“…Another study utilizing the green method for the fabrication of silver-zinc oxide nanocomposite showed that the mean diameter was 62.5 nm and synthesized NCs have toxic effects against cancer cells [89]. According to researches, ZnO NPs' selective cell toxicity against cancerous cells can be the consequence of the pH-dependent dissolution of ZnO into Zn 2+ ions under an acidic intracellular environs, which can lead to oxidative stress due to generation of ROS [90][91][92][93]. ROS could also facilitate cell death using external apoptosis and necrosis [94].…”
Section: Cellular Toxicity Influence Of Prepared Npsmentioning
confidence: 99%